Advanced approaches and applications of energy footprints toward the promotion of global sustainability. (1st March 2020) - Chen, Shaoqing; Kharrazi, Ali; Liang, Sai; Fath, Brian D.; Lenzen, Manfred; Yan, Jinyue
Abstract: Ever-increasing energy demands pose huge environmental challenges globally. The strategies and methods that are chosen to address the energy crisis will, in part, determine the possibility of fulfilling the 1.5-degree global warming target set by the Paris Agreement, and of achieving the United Nations Sustainable Developmental Goals, two vital and ambitious objectives for humans in the coming decades. While numerous inventory and modelling approaches have been developed to evaluate direct and indirect energy requirements at multiple scales from industries to cities and to the global economy, a discussion on their implications for environmental sustainability is long overdue. In this study, we provide an overview of the research paradigm and the important approaches that have been developed to address energy sustainability and review the papers included in this Special Issue, which are representative of some of the major advancements in energy, carbon, and other hybrid footprint approaches. This Special Issue aims to gather and harmonize state-of-the-art energy accounting frameworks, models, and metrics that benefit the promotion of global sustainability.